Understanding interaction rituals: The impact of interaction ritual chains of the live broadcast on people’s wellbeing - Meng, Lu; Zhao, Yijun; Jiang, Yushi; Bie, Yongyue; Li, Jingpeng (Frontiers in Psychology, 2022)
With the global pandemic of COVID-19, it has been striking psychological burdens on individuals. Under this background, more and more people get well-being by watching live broadcasts. However, the psychological mechanism behind this phenomenon is still a "black box”. This study finds that when people watch a live-broadcast and interact with anchors and other people, an interaction ritual chain is formed, and emotional energy is generated, thus making people experience and understand the meaning of the live interaction ritual chains. Under the effect of the meaning transfer model, people will generate well-being. Specifically, the basic meaning of live interaction (emotional meaning and functional meaning) drives people's generation of well-being. The meanings of self-participation, self-display, self-concept, and self-renewal play a role in mediation in enhancing people's well-being with the basic meaning of live broadcast interaction.